2007
DOI: 10.1130/g24224a.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the global carbon cycle occurred as two episodes during the Permian–Triassic crisis

Abstract: Coeval records of ocean, atmosphere, and terrestrial change are crucial to understanding the pattern and causes of global mass extinction across the Permian-Triassic boundary (PTB). However, relationships among changes in different settings remain largely unclear, primarily due to the challenges associated with the correlation among disparate records. Here we compare marine carbon isotopic records with marine and terrestrial environmental and biotic events recorded in sediments from the Meishan PTB section of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
188
2
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(214 citation statements)
references
References 27 publications
11
188
2
13
Order By: Relevance
“…Above this perturbation, δ 13 C (carb) remains at ∼1‰ for the remainder of the Griesbachian. The negative excursion within bed 39 at Meishan was not recognized by Cao et al (11) or Xie et al (17) due to sample spacing, although more closely spaced sampling reported in Song et al (31) recovers it. The second excursion is possibly correlative with one seen in the GK-1 core from the Carnic Alps (32), although this excursion cannot yet be confirmed as a global signal or to be useful in correlation.…”
Section: New Age Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…Above this perturbation, δ 13 C (carb) remains at ∼1‰ for the remainder of the Griesbachian. The negative excursion within bed 39 at Meishan was not recognized by Cao et al (11) or Xie et al (17) due to sample spacing, although more closely spaced sampling reported in Song et al (31) recovers it. The second excursion is possibly correlative with one seen in the GK-1 core from the Carnic Alps (32), although this excursion cannot yet be confirmed as a global signal or to be useful in correlation.…”
Section: New Age Modelmentioning
confidence: 78%
“…To better understand the relationship between environmental perturbation and biotic response, accurate and precise age models that integrate geochronology, paleontology, and geochemistry must be developed (8,11,16,17). Recognition of astronomically forced sedimentary cycles (Milankovitch cycles) in late Permian and Triassic sedimentary rocks tuned with available geochronology have been used to refine existing age models of the biotic crisis (18)(19)(20).…”
Section: ± 028 Ma (54)mentioning
confidence: 99%
“…It has been extensively documented that the endChanghsingian mass extinction is associated with a worldwide sharp negative shift of d 13 C. According to the Meishan section (Xu and Yan, 1993;Cao et al, 2002Cao et al, , 2009Riccardi et al, 2006;Xie et al, 2007), both d 13 C carb and d 13 C org began to decrease at the base of Bed 23, which is nearly at the base of the Clarkina yini Zone. The most negative value is at the topmost part of Bed 24 within the Clarkina meishanensis Zone, which is immediately below Bed 25 of 252.25 AE 0.06 Ma and associated with the most severe biotic mass extinction.…”
Section: C Carb Isotopementioning
confidence: 99%
“…Thus, nutrient exchange in the water column can trigger a series of biogeochemical processes among different GFGs, which significantly affect marine environments. The presence of a variety of GFGs and the associated marine environmental changes across the Permo-Triassic boundary represented such a case in Earth history [130,131,165,174].…”
Section: Gfgs Related To Nutritional Statusmentioning
confidence: 99%
“…end Permian and end Cretaceous), in addition to the associated major climate change [165,166]. Stanley [167] proposed that the dominant cause for carbon isotope excursions was associated with the Phanerozoic mass extinctions is change in the respiration rate of marine bacteria.…”
Section: Gfgs Involved In Abnormal Climatementioning
confidence: 99%